Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/bjs.5600
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and prognosis of gastric cancer in young European adults

Abstract: Gastric cancer in young adults tends to be more advanced; however, when matched for stage, the prognosis does not differ from that of older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
110
6
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 15 publications
21
110
6
2
Order By: Relevance
“…GC patients younger than 40 years are rare; approximately 2-16.2% of GC occurs in patients younger than 40 years old (Santoro et al, 2007;Kuling et al, 2008;Dhobi et al, 2013), and only 1.1-3.3% of cases occur in patients younger than 30 years of age (Lim et al, 2003). The preponderance of evidence showed that there are differences in the clinicopathological features and molecular mechanism of gastric carcinoma between young and older patients (Quispe et al, 2000;Lim et al, 2003;Hajmanoocheri et al, 2013a;2013b).…”
Section: Clinicopathological and P53 Gene Alteration Comparison Betwementioning
confidence: 99%
See 1 more Smart Citation
“…GC patients younger than 40 years are rare; approximately 2-16.2% of GC occurs in patients younger than 40 years old (Santoro et al, 2007;Kuling et al, 2008;Dhobi et al, 2013), and only 1.1-3.3% of cases occur in patients younger than 30 years of age (Lim et al, 2003). The preponderance of evidence showed that there are differences in the clinicopathological features and molecular mechanism of gastric carcinoma between young and older patients (Quispe et al, 2000;Lim et al, 2003;Hajmanoocheri et al, 2013a;2013b).…”
Section: Clinicopathological and P53 Gene Alteration Comparison Betwementioning
confidence: 99%
“…Gastric cancer is one of the most common gastrointestinal malignancies worldwide and every year ~1 million new cases of GC are diagnosed and 740,000 die of this disease worldwide (Parkin et al, 2005;Santoro et al, 2007;Ferlay et al, 2013;Guggenheim et al, 2013;Karim et al, 2013). Although recent developments in medical screening has decreased the incidence of advanced GC, still GC in youngsters remains a serious problem as routine screening in many countries including India does to diagnose in young people and is asymptomatic even in the advanced stages of the disease (IARC, 2001;Isobe et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have addressed the absence of positive family history in elderly gastric cancer patients [2] as compared to patients aged 45 years or less [3,10]. In Western countries, a hereditary type of diffuse, poorly-differentiated, infiltrative adenocarcinoma has been described in young patients.…”
Section: Family Historymentioning
confidence: 99%
“…Factors that contribute to the poor prognosis of gastric cancer in the young include delayed detection, resulting in an advanced stage at presentation, diffuse infiltration of the tumor and a poorly differentiated histology [1,4,10]. On the other hand, recent studies have indicated that prognosis in young patients is equivalent to [7,11,12] or better than that in middle-aged patients with cancers at the same stage [8,9,13,14]. Thus, the concept of gastric cancer having a poorer prognosis in relatively young patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%